2007
DOI: 10.1016/j.wocn.2006.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Free classification of regional dialects of American English

Abstract: Recent studies have found that naïve listeners perform poorly in forced-choice dialect categorization tasks. However, the listeners' error patterns in these tasks reveal systematic confusions between phonologically similar dialects. In the present study, a free classification procedure was used to measure the perceptual similarity structure of regional dialect variation in the United States. In two experiments, participants listened to a set of short English sentences produced by male talkers only (Experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 29 publications
7
75
2
Order By: Relevance
“…Unlike the techniques used in the literature reviewed above, the methods and techniques described below do not require any specialized software or programming skills beyond what is typically available in speech research laboratories, and can therefore be applied to new research questions by both students and more senior researchers. To make the methods more concrete, they are described in the context of an example set of data that was obtained in an unpublished follow-up study to the experiments reported by Clopper and Pisoni (2007). The stimulus materials in the present example were identical to those used in Clopper and Pisoni's Experiment 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the techniques used in the literature reviewed above, the methods and techniques described below do not require any specialized software or programming skills beyond what is typically available in speech research laboratories, and can therefore be applied to new research questions by both students and more senior researchers. To make the methods more concrete, they are described in the context of an example set of data that was obtained in an unpublished follow-up study to the experiments reported by Clopper and Pisoni (2007). The stimulus materials in the present example were identical to those used in Clopper and Pisoni's Experiment 2.…”
Section: Methodsmentioning
confidence: 99%
“…When the number of groups is not predetermined, a similar set of analyses on the number of groups produced (including mean, median, and range) can also be computed (see Clopper & Pisoni, 2007). The second set of analyses focused on the perceptual similarity of the talkers and included two types of models: clustering and multidimensional scaling (MDS).…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of an unconstrained free classification task, where listeners' are able to provide their own labels, has a number of advantages over a forced-choice task. First, the constraints imposed by the researchers in a forced-choice task, by its very design, i.e., providing a limited selection of countries or speech varieties, restricts listeners from creating their own categorisations (Clopper & Pisoni, 2007b). The present study attempts to extend our understanding of non-linguists' perceptions of linguistic diversity through the investigation of how accurately and consistently UK-born, native English speaking university students can identify speaker place of origin of specific varieties of L1 English varieties spoken in the UK, as well as a range of L2 English forms spoken by overseas students at the university in question (see below).…”
Section: One Of the Earliest Studies Conducted Amongst Native Englismentioning
confidence: 99%
“…1 As with the previous two questions, there is some evidence that listeners can in fact make these sorts of socio-indexical inferences on the basis of speech alone (for a review, see Thomas, 2002). For instance, listeners can classify talker's regional dialect at above-chance accuracy based on a short except of their speech (a single sentence read from a standard set Clopper & Pisoni, 2006;Clopper & Pisoni, 2007). We include a talker's identity as a socio-indexical variable (in the sense of what individual person they are).…”
Section: Question 3: How Well Could Listeners Infer Socio-indexical Vmentioning
confidence: 99%